Pelatihan Keterampilan Pembuatan Produk Nata De Leri di Kampung Nanas Palangka Raya: Training Skill to Making Nata De Leri Products in Kampung Nanas Community Palangka Raya - Krestina, Widya; Permatasari, Silvani; Malinda, Okta; Seiya, Saint; Ramadhani, Ahmad (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Nata is a product of fermentation by bacteria Acetobacter xylinum on a substrate containing sugar such as coconut water, pineapple juice or other fruit juice, which uses some of the glucose for metabolic activities and the other part is broken down into a polysaccharide known as extracellular cellulose in gel form. This service is carried out for the people of Kampung Nanas by providing practical training and assistance aims to provide skills to the residents to diversify pineapple product from their plantations which are fermented with a mixture of rice washing water waste, ZA/sprouts, and other ingredients. -Other ingredients become nata which can later add economic value and increase income for the local community. Training is carried out using the experimental learning method. The training began with a presentation and then direct practice in making nata de leri. This activity has stages of preparing tools and materials, providing education through pocket books, direct practice in making nata de leri and harvesting on the 10th day. The taste test results show that 90% really like it, 5% like it and 5% quite like it, the level of texture elasticity shows that 75% are very chewy, 15% are chewy, and 10% are quite chewy, while for color 60% say they are very attractive and 40% are attractive because it’s white.